Determining the Influence of the Quality of Financial Statements of MSMEs in Sleman: Determining the Influence of the Quality of Financial Statements of MSMEs in Sleman - Budiantara, Martinus; Paramitalaksmi, Ratri; Maharani, Desak Putu (Program Sarjana Terapan Universitas Islam Indonesia, 2024)
The purpose of this study was to find: (1) t the effect of Accounting Comprehension on the quality of MSMEs financial statements moderated by self efficacy. (2) he effect of MSMEs digitalization on the quality of MSMEs financial statements moderated by self efficacy. (3) the effect of MSMEs financial Inclusion on the quality of MSMEs financial statements moderated by self efficacy. The methodology used in this research is quantitative. The sample of the study were 103 MSMEs entrepreneurs in Sleman, Special Region of Yogyakarta.Accounting Comprehension, MSMEs Digitalization and MSMEs Financial Inclusion have a significant effect on the Quality of MSMEs Financial Statements in Sleman even though the Self-Efficacy is not able to moderate these three variables on the Quality of MSMEs Financial Statements.